First neutron studies of the magnetism and rattling modes in CePt4Ge12. (18th March 2015) - Galéra, R M; Opagiste, C; Amara, M; Zbiri, M; Rols, S
Abstract: The filled skutterudite CePt4 Ge12 is reported to be at the border between an intermediate valence (IV) state and a Kondo lattice behavior. We report here the first inelastic neutron scattering experiments, carried out on the Ce compound and its non-magnetic counterpart LaPt4 Ge12 . Prior the neutron studies, the structural and magnetic properties of both samples have been determined. Inelastic neutron scattering spectra are dominated by phonon contribution for both compounds. A rattling vibration mode is observed at 6.9 meV and 7.5 meV for the Ce and La compounds, respectively. In CePt4 Ge12 no crystal field excitation could be resolved. Only a small and wide extra contribution at high energy (22-28 meV) is observed. This result would be more consistent with an IV behavior.